IMPLEMENTASI PROGRAM EMAS (EXPANDING MATERNAL AND NEONATAL SURVIVAL) SEBAGAI UPAYA PENURUNAN ANGKA KEMATIAN IBU DAN BAYI BARU LAHIR DI KABUPATEN TEGAL - fifien luthfia rahmi; nunik retno h; ahmad taufiq (Journal of Politic and Government Studies, 2016)
ABSTRACT Research about Implementation of EMAS (Expanding Maternal and Neonatal Survival) program as efforts to Decrease death rate of mother and newborn baby in Tegal aimed to review implementation of EMAS Program in Tegal regency. In addition, this research also has a purpose to review the obstacles appeared in implementation of EMAS Program in Tegal regency. This study using implementation theory of Donald S. Van Meter and Carl E. Van Horn, especially the factors affected the implementation of a program. Methods used in this Research is qualitative descriptive methods as data collection methods which are completed through an interview and observations. Informants engaged by researcher are the Secretary of the Working Group (WG) EMAS Tegal, Team Leader of EMAS Tegal, Secretary of Civil Society Forum (FMM) Tegal, Strengthening Civil Society Coordinator (CSSC) EMAS Tegal, Provincial Team Leader gold Central Java Province, Head of Budget Planning Department Of Regional Planning And Development Agency (Bappeda) Tegal regency , health worker at Tarub health center, dr. Soeselo Hospital And Islamic PKU Muhammadiyah Hospital and Tegal society as recipients of mother and newborn baby health service. Results showed factors affecting the implementation of EMAS Program in Tegal regency and restricted factors appearing in EMAS Program Implementation in Tegal regency. Based on result of this research, can be concluded that the implementation of EMAS Program in Tegal haven’t reached the targets to reduce mother and newborn baby death rate by 25%. From this facts, there are some aspects that need more attention. The result of this research expected to provide materials for government and stakeholder to evaluate implementation of EMAS program, so in the Future the death rate of mother and newborn baby in Tegal can be decreased.Keyword : Program Implementation, EMAS of Tegal Regency, Mother and Newborn Baby.